THE ROLE OF PLASTICS IN ORTHODONTICS ORTHODONTIC APPLIANCES - Madalina Matei; Alina Ramona Dimofte; Grigore Ionuta; Gabriel G. Condurache; Iolanda Florentina Dumitru; Scutariu Mihaela-Monica; Ana Maria Zaharescu; Gabi Topor (Romanian Society of Oral Rehabilitation, 2020)
Orthodontics is a branch of dentistry that addresses the etiopathogenesis, clinic, diagnosis and various methods of treatment of dento-maxillary anomalies. The importance of Orthodontics as a study subject has increased, due to the increased number of dento-maxillary anomalies, which have direct consequences on craniofacial function and morphology and indirect on the general development of the body, but especially on the subject's psychology regarding its integration into society. Childhood and adolescence consist of sensitive growth periods including the pediatric dentist encountering multiple challenges in terms of cooperation, adherence to treatment, and the patient's family. Dento -maxillary anomalies are conditioned by the development of the child in the embryonic period by the reproductive characters, as well as by the growth disorders in the post-embryonic period, from birth to the end of the adult development phase. Growing patients have a varied pathology, represented by: caries, dento-periodontal trauma, dental abnormalities, which may require prosthesis Specific characteristics of plastics determine, and will determine, the realization of products at a high quality level, with high technological performance and reliability. If they are used as restraints, only retention is needed. They are called plastics material produced on a polymer base capable of heating and to take the given form and to keep it after cooling. According to the quantity in which they are produced, they occupy the first place among the polymeric materials. They are characterized by high mechanical strength, low density, high chemical stability, thermal insulation and electrical insulation properties.